Deixis in Bahasa Tae' and English: A Pragmatics Contrastive Analysis - Magfirah Thayyib (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
Deixis in Bahasa Tae' and English: A Pragmatics Contrastive Analysis